2021
DOI: 10.1177/23259671211038893
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents Have Twice the Revision Rate of Young Adults After ACL Reconstruction With Hamstring Tendon Autograft: A Study From the Swedish National Knee Ligament Registry

Abstract: Background: Previous studies have identified young age as a risk factor for anterior cruciate ligament (ACL) revision. However, few studies have looked separately at pediatric patients and adolescents with regard to outcomes after ACL reconstruction. Purpose: To determine whether patient age at ACL reconstruction affects the risk of undergoing revision surgery in young patients. Study Design: Cohort study; Level of evidence, 3. Methods: This study was based on data from the Swedish National Knee Ligament Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Current literature reports better results, in terms of patient-reported outcomes and risk of ACL revision, after anterior cruciate ligament (ACL) reconstruction in adults [1][2][3][4] compared with ACL reconstruction in children and adolescents [5][6][7][8][9]. Outcomes in youth ACL literature vary widely [10] and there are very few, if any, studies published with a large cohort of patients that primarily focus on patient-reported outcomes after ACL reconstruction in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Current literature reports better results, in terms of patient-reported outcomes and risk of ACL revision, after anterior cruciate ligament (ACL) reconstruction in adults [1][2][3][4] compared with ACL reconstruction in children and adolescents [5][6][7][8][9]. Outcomes in youth ACL literature vary widely [10] and there are very few, if any, studies published with a large cohort of patients that primarily focus on patient-reported outcomes after ACL reconstruction in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…25 This stands in contrast to a study done using the Swedish registry data which found an overall revision rate after ACLR of 1.1% and 2.6% at 2 years and 5 years respectively. 26 The authors note that patients may have been exposed to less sporting activity which may help explain their low revision rate compared to others noted in the pediatric and adolescent literature. The median age of our patients in this study was 16 years with an average time to reoperation for revision ACLR of 16.6 months and contralateral ACLR of 22.1 months.…”
Section: Discussionmentioning
confidence: 85%
“…In young active patients, the risk of reconstruction failure increases with higher activity levels. 1 A variety of different methods are used to define return to activity. Return to activity may involve a patient returning to casual, amateur, or competitive level of sport, or analyzing scores calculated from an activity questionnaire such as the Marx Activity Questionnaire or the Tegner Activity Scale.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructing the ACL-deficient knee may also reduce the risk of long-term complications due to instability, such as injury to the menisci and cartilage. 1 , 2 Additionally, reconstruction has been shown to be economically advantageous with an increase in quality-of-life compared to rehabilitation and non-operative management. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%